2022
DOI: 10.1038/s41529-022-00252-2
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic effects on transgranular chloride-induced stress corrosion crack propagation of arc welded austenitic stainless steel

Abstract: The effect of crystallography on transgranular chloride-induced stress corrosion cracking (TGCISCC) of arc welded 304L austenitic stainless steel is studied on >300 grains along crack paths. Schmid and Taylor factor mismatches across grain boundaries (GBs) reveal that cracks propagate either from a hard to soft grain, which can be explained merely by mechanical arguments, or soft to hard grain. In the latter case, finite element analysis reveals that TGCISCC will arrest at GBs without sufficient mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…Moreover, the cracks appear to propagate along grains having alternating high and low mechanical hardness. This behavior is consistent with previously reported observations that crystallographic hardness-namely, Schmid (m) and Taylor (M) factor mismatch-control the crack propagation tendency in 304L stainless steel welds [27]. Specifically, our previous work showed that cracks tend to propagate either from crystallographically hard to crystallographically soft grains (i.e., high m, low M grains to low m, high M grains), or vice versa.…”
Section: Hardness Mapping and Individual Grain Analysis With Nanoblitzsupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, the cracks appear to propagate along grains having alternating high and low mechanical hardness. This behavior is consistent with previously reported observations that crystallographic hardness-namely, Schmid (m) and Taylor (M) factor mismatch-control the crack propagation tendency in 304L stainless steel welds [27]. Specifically, our previous work showed that cracks tend to propagate either from crystallographically hard to crystallographically soft grains (i.e., high m, low M grains to low m, high M grains), or vice versa.…”
Section: Hardness Mapping and Individual Grain Analysis With Nanoblitzsupporting
confidence: 92%
“…The bent coupon was sectioned by diamond saw into a smaller piece for ease of metallographic polishing; the section piece contained a cross-section of the weld, heat-affected zone (HAZ), and base metal, as represented by the blue dashed lines in Figure 1c. From our earlier study [27], the HAZ was found to be most susceptible to CISCC, and thus, this study focused only on the HAZ. The sectioned piece was polished following standard metallurgical sample preparation processes [50] and finished with 12 h of vibratory polishing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Grains with a high Taylor factor are more resistant to plastic deformation than those with a low Taylor factor, making crack deflection or termination easy to occur when there is a large Taylor factor mismatch between adjacent grains. [ 26 ] In Figure 11b, grain I, with a high Taylor factor (3.6), behaves as a “hard” grain, while grain II, with a low Taylor factor (2.5), behaves as a “soft” grain. Due to the large Taylor factor mismatch (1.1) between these two grains, cracks can hardly pass through the grain boundary of the “hard” grain (grain I), resulting in crack deflection.…”
Section: Resultsmentioning
confidence: 99%